A systematic assessment of the pro-poor reach of development bank investments in urban sanitation - Hutchings, Paul; Johns, M.; Jornet, D.; Scott, C.; van den Bossche, Z. (IWA Publishing, 2018)
This paper presents an assessment of development banks’ investment in urban sanitation between 2010 and 2017. It reveals an overall increase in investment, yet this falls short of bridging the significant financing gap in the sector. The paper also assesses the major areas of investment to show that, on the infrastructure side, 20 times more money is invested in sewerage than faecal sludge management, while on the enabling environment side, institutional capacity building is the most financed area. Using a new pro-poor assessment tool, an appraisal was made of the extent to which the investments were pro-poor. This analysis indicates that over half of investments, where an assessment could be made, were considered to be pro-poor, yet the use of the assessment tool reflects a lack of information within development bank reporting on the pro-poor nature of investments. Going forward, improving how development banks report on the pro-poor character of their investments would be a useful step for helping the sector assess the effectiveness of investments. The paper concludes by arguing that, despite progress, development banks should be even more ambitious in seeking to support pro-poor urban sanitation investments if the world is to overcome the urban sanitation challenge.
Keywords: development bank; finance; pro-poor; urban sanitation